Positively selected enhancer elements endow osteosarcoma cells with metastatic competence - Morrow, James J. (Nat Med, 2018)
Metastasis results from a complex set of traits acquired by tumor cells, distinct from those necessary for tumorigenesis. Here, we investigate the contribution of enhancer elements to the metastatic phenotype of osteosarcoma. Through epigenomic profiling, we identify substantial differences in enhancer activity between primary and metastatic tumors in human patients as well as near-isogenic pairs of high and low lung-metastatic osteosarcoma cells. We term these regions Metastatic Variant Enhancer Loci (Met-VELs). Met-VELs drive coordinated waves of gene expression during metastatic colonization of the lung. Met-VELs cluster non-randomly in the genome, indicating that activity of these enhancers and their associated gene targets are positively selected. As evidence of this causal association, osteosarcoma lung metastasis is inhibited by global interruptions of Met-VEL-associated gene expression via pharmacologic BET inhibition, by knockdown of AP-1 transcription factors that occupy Met-VELs, and by knockdown or functional inhibition of individual genes activated by Met-VELs, such as coagulation factor III/tissue factor (F3). We further show that genetic deletion of a single Met-VEL at the F3 locus blocks metastatic cell outgrowth in the lung. These findings indicate that Met-VELs and the genes they regulate play a functional role in metastasis and may be suitable targets for anti-metastatic therapies.